2 - Développement dépendant et paupérisation de la paysannerie : le cas de l'Afrique du nord - Dr. Fredj STAMBOULI, (Africa Development, 1982)
Rural poverty in Maghreb is not a natural phenomemon at all. It is not only the outcome of a long historical process characterized by stagna- tion but also that of the entry of colonial powers into this already weak area . Drawing a general picture of this part of Africa , the author stresses the weakness of its structure (low agricultural surplus , unstable , not quite settled social communities ) which puts it at the mercy of the imperialistic cultures. The resultant capitalistic mode of dependence widened the gap between urban and rural areas and generated a rural impoverishment ßocked-in rural structures and exploitation of cheap labour - in the form domestic services and in other sectors of employment - to the advantage of the dominant capitalistic sector). In his description of the social system which was confronted with the imperialistic expansion and colonization, the author states that it was a heterogenous but integrated society - with a strong solidarity system and a capacity for self-sufficiency - i.e. able to control its own wealth for a long time. The impacts of the penetration of imperialism and colonialism in this society were: a large scale alienation of land which deeply affected the pea- santry an impoverishment aggravated by a strong demographic pressure. After independence the situation hardly improved. There were no radical changes in the existing structures. Today there is what the author calls an insurmountable contradiction between the unavoidable centrali- zation of the state - caused by an advanced technology - and a self- sufficient community. Fredj STAMBOULI, Professeur - Université de Tunis.